Synthesis and Characterization of Some New Morpholine Derivatives (Baghdad Science Journal, 2016)
In this paper a new series of morpholine derivatives was prepared by reacting the morpholine with ethyl chloro acetate in the presence triethylamine as a catalyst in benzene gave morpholin-N-ethyl acetate(1) which reacted with hydrazine hydrate in ethanol, and gave morpholin-N-ethyl acetohydrazide (2) . Morpholin-N-aceto semithiocarbazide (3) were prepared by reacting compound(2) with ammonium thiocyanate , concentrated hydrochloric acid and ethanol as a solvent .Compound (3) reacted with sodium hydroxide and hydrochloric acid to give 5-(morpholin-N-methylene)-1H-1,2,4-triazole-3-thiol (4) .The new series of 1,2,4-triazol derivatives (5-8) was synthesized by reaction of compound(4) with formaldehyde , DMF as a solvent and different secondary amines. Preparation of new 1,2,4-triazoline derivatives (9) by reaction compound (4) with bromo acetic acid . Reaction of compound (9) with different aromatic aldehyde and dimethyl sulfoxide as a solvent obtained compounds (10-13).